MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN ORIGAMI DI KELOMPOK B TK PERTIWI TELUK KUANTAN - ', Darmawati; ', Mahdum; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on observation, the development of children in kindergarten Pertiwi Teluk Kuantan found any constraints on fine motor activities that most children are still difficulties in fine motor activities, especially folding or origami. There are some children who are reluctant to perform fine motor activities there is also a crying study results should be given to children less optimal. Because of that learning that can improve fine motor skills anak.Penelitian aims to determine the effect of origami activities against the fine motor skills Children ages 5-6 year in the Gulf of TK Pertiwi Kuantan. Sampel used in this study 15 children. The data collection techniques used are observasi.Penelitian including quantitative and kualitatif. In quantitative research collected data were analyzed descriptively presentase. Hipotesis research is found influence signifikan terhadap fine motor skills of children after conducting this origami. Hal can diketahui daari analysis results average obtained that before action is taken at 28.89% after the action in the first cycle an average yield of 40.56% of the traffic system and after the action on the second cycle of the traffic system increased by 84.35%. So we can conclude that there are differences in the fine motor skills of children significantly after conducting origami. So, the means origami activities may increase the fine motor skills of children aged 5-6 years grouped B TK Pertiwi Singingi Kuantan District Kuantan bay.Keywords: Fine Motor Ability, Activity Origami